Influential Elements of The Market. The Case of the Textile Loom Production Association of El Oro, Asoprotexteo - Cuzco-Beltrán, Raquel Patricia (2021)
In this research, each of the components of the market was evidenced, which resulted in the objective of analysing the influential elements of the market: Asoprotexteo gold loom textile production association case, the approach of the market study had a descriptive methodology including surveys directed to 89 people from different social strata of the city of Machala, where questions were raised based on consumer occupation, supply, demand, price and distribution channels, it was also evidenced as results that in the process of sales it is essential to know the customers, needs and their purchase decision, so that the company gets to succeed in commercial activities. It was concluded that by knowing the behaviour of consumers, the company established a comparison, analysis and relationship of the results obtained, thus making it easier to apply market strategies and build customer loyalty.